Pharmacotherapy of scleritis: current paradigms and future directions - Beardsley, Robert M; Suhler, Eric B; Rosenbaum, James T; Lin, Phoebe (Expert opinion on pharmacotherapy, 2013)
Scleritis is an inflammatory condition affecting the eye wall that may be associated with a number of systemic inflammatory diseases. Because scleritis can be refractory to standard treatment, knowledge of the body of available and emerging therapies is paramount and is reviewed here. This review focuses on both traditional and emerging therapies for noninfectious scleritis. The authors cover the mechanisms of action and potential adverse effects of each of the treatment modalities. In addition, a summary of the significant MEDLINE indexed literature under the subject heading 'scleritis', 'treatment', 'immunomodulator' will be provided on each therapy, including commentary on appropriate use and relative contraindications. Novel treatments and potential drug candidates that are currently being evaluated in clinical trials with therapeutic potential will also be reviewed. While oral nonsteroidal anti-inflammatory drugs and oral corticosteroids are widely used, effective, first-line agents for inflammatory scleritis, refractory cases require antimetabolites, T-cell inhibitors, or biologic response modifiers. In particular, there is emerging evidence for the use of targeted biologic response modifiers, and potentially, for local drug delivery.